SMART UNIVERSITY IMAGE: FROM BRANDING TO MARKETING STRATEGY IN PRIVATE UNIVERSITIES - Senny Luckyardi; Ratih Hurriyati; Disman Disman; Puspo Dewi Dirgantari (Jurnal Riset Bisnis dan Manajemen, 2023)
The objective of the research is to analyze how Smart University Image can be a marketing strategy in private universities. The paper proposed a revised construct of brand image in smart university domain that is Smart University Image (SUI). The new construct of SUI will contribute to more appropriate university marketing strategy in highly competitive market in digital era. In addition, the research is aimed to discover SUI influence toward students’ satisfaction. This study employed a quantitative methodology, supported by study literature. Structural Equation Method is applied to analyse relationship between variables. The paper reveals that SUI able to increase student satisfaction by mediating it from Value Co Creation. It also means that SUI can be used as marketing strategy by promoting advanced technology toward Gen Z as the student’s candidate. Furthermore, the proposal of a new construct, namely SUI, becoming a more appropriate and integrated term for marketing strategy in the SU domain.